Otimização dos parâmetros de monopolos planares de microfita para aplicações em sistemas de banda ultra larga - Nóbrega, Clarissa de Lucena (2008)
This work presents a theoretical and experimental investigation about the properties of microstrip antennas for ultra-wideband systems. Configurations of elliptic monopoles with different eccentricities and circular monopoles are considered. Two prototypes for each antenna configuration were built, one with the typical microstrip configuration and the other is similar to the first, except for a small aperture in the ground plane. Therefore, this work proposes to modify the configuration of the ground plane of the monopoles designed adding a rectangular stub, in order to optimize and improve the performance of such structures. The obtained results show that the introduction of that rectangular aperture in the ground plane allows an improvement of the frequency response for the considered antenna propotypes. It is observed a good agreement between the measured and simulated results. Finally, some proposals for future works are presented